If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -8p = 9 Solving 7 + -8p = 9 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -8p = 9 + -7 Combine like terms: 7 + -7 = 0 0 + -8p = 9 + -7 -8p = 9 + -7 Combine like terms: 9 + -7 = 2 -8p = 2 Divide each side by '-8'. p = -0.25 Simplifying p = -0.25
| 4+-2(2x+-7)=-6 | | 4-2(2x-7)=-5 | | 18p^2-55=30p-7 | | 8+2x=x+3 | | 8-2x=x+3 | | x-3+x=121 | | v^2+1=v | | 17+3x=(5-x) | | 4k^2+60k+216=0 | | 4n^2+16=-20n | | q=-7x^2+6x+4 | | (n-4)(n-5)=0 | | 10d-22+6y=12d+10 | | mn-x=m | | 0=4x^2-5x-5 | | 0=4x^2+5x-5 | | p=-5x^2+6x+6 | | x+36=x*4 | | 8x+2y+26=10 | | 13x^2+8x-22=0 | | 6+25x=20x+10 | | 5x+2(x+5)=52 | | f(x)=0.7 | | 4+7x=16+x | | (5x)(6y)= | | 6x-3=16x-38 | | 2ln(x+5)=4 | | 100+0.5*(Y-200)+250+200+150= | | 8X+13=-15 | | 2=x-3x+35 | | y=92+-13x | | 5(5p-3)= |